Factors affecting asset price expectations: Fundamentals and policy - Nico Valckx (Bank of Finland, 2001)
This paper examines what factors move US and European stock and bond markets, extending earlier work by Campbell and Ammer (1993). Inflation news is incorporated into the stock and bond decomposition and explicit attention is given to different horizons over which expectations are formed.Sensitivities to monetary policy instruments and fundamental factors are examined. The data are monthly.For the euro area, a unique data set is constructed.The results illuminate a number of widely-held pre-conceptions and confirm that inflation news volatility is a non-trivial factor in the stock and bond return decompositions.
URN:NBN:fi:bof-20140807294
Keywords: 330; stock prices; bond prices; return decompositions; fundamental factors